2020
DOI: 10.1111/bjd.19300
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhidrosis Quality of Life Index (HidroQoL©): further validation and clinical application in patients with axillary hyperhidrosis using data from a phase III randomized controlled trial*

Abstract: Summary Background The Hyperhidrosis Quality of Life Index (HidroQoL©) is a validated patient‐reported outcome measure capturing the quality of life of people affected by hyperhidrosis. Objectives We aimed to extend the validity evidence to physician‐confirmed diagnosis of primary axillary hyperhidrosis. Methods Data from a phase III randomized placebo‐controlled clinical trial were used (n = 171). Confirmatory factor analysis was carried out to confirm the a priori two‐factor structure of the HidroQoL. Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Questions are rated on a 3‐point scale and a summary score for each domain and overall score is calculated. In 2020, the HidroQoL was revalidated specifically for primary axillary HH and the minimally clinically important difference (MCID) for treatment response has been defined as an improvement of ≥ 4 points 26 …”
Section: Methodsmentioning
confidence: 99%
“…Questions are rated on a 3‐point scale and a summary score for each domain and overall score is calculated. In 2020, the HidroQoL was revalidated specifically for primary axillary HH and the minimally clinically important difference (MCID) for treatment response has been defined as an improvement of ≥ 4 points 26 …”
Section: Methodsmentioning
confidence: 99%
“…Five included studies reported on the DLQI [3,26,41,43,46]; three on the HQLQ [1,6,35], the HidroQoL [9,18,20] and the HDSS [39,46,47], respectively; two on the SF-36 [38,46], the Hyperhidrosis Disease Severity Measure-Axillary (HDSM-Ax) [16,22], as well as the Hyperhidrosis Scale (HS) [21,35]; and one each on the ASDD and its child version (ASDD-C) [34], the Hyperhidrosis Impact Questionnaire (HHIQ) [25], the Illness Intrusiveness Rating Scale (IIRS) [5], the Hyperhidrosis Questionnaire (HQ) [24], the Sweating Cognitions Inventory (SCI) [52] and the Table 3 GRADE approach for grading the quality of evidence [36] Starting point: assumption that the evidence is of high quality. Information on how to downgrade is described in the COSMIN user manual [31].…”
Section: Resultsmentioning
confidence: 99%
“…Both reports showed ceiling effects for most of the items. According to Gabes et al [9], 26-91% of the patients chose the highest response category. Floor effects were found by Kamudoni [18] for 13 items of the HidroQoL.…”
Section: Information On Interpretability and Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations